2018
DOI: 10.1371/journal.pone.0191493
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural networks show an equivalent and often superior performance to dermatologists in onychomycosis diagnosis: Automatic construction of onychomycosis datasets by region-based convolutional deep neural network

Abstract: Although there have been reports of the successful diagnosis of skin disorders using deep learning, unrealistically large clinical image datasets are required for artificial intelligence (AI) training. We created datasets of standardized nail images using a region-based convolutional neural network (R-CNN) trained to distinguish the nail from the background.We used R-CNN to generate training datasets of 49,567 images, which we then used to fine-tune the ResNet-152 and VGG-19 models. The validation datasets com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 16 publications
1
131
0
1
Order By: Relevance
“…Again, the combined performance was on par with dermatologists and outperformed non-dermatologists. R-CNNs have been used in fracture detection in radiology [55] and the detection of the nail plate in onychomycosis [56]. Algorithms could potentially detect and diagnosis skin cancer without any preselection of suspicious lesions by dermatologists.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the combined performance was on par with dermatologists and outperformed non-dermatologists. R-CNNs have been used in fracture detection in radiology [55] and the detection of the nail plate in onychomycosis [56]. Algorithms could potentially detect and diagnosis skin cancer without any preselection of suspicious lesions by dermatologists.…”
Section: Non-melanoma Skin Cancermentioning
confidence: 99%
“…This is a notable limitation considering that the incidence of scalp psoriasis is 45-56% and nail psoriasis is 23-27% among psoriatic patients [57]. CNNs have been created for other diseases, such as atopic dermatitis [58], onychomycosis [56], and rosacea [59]. To classify onychomycosis, Han et al [56] used a R-CNN to generate a training datasets of 49,567 images of nails and found that a combination of their datasets performed better than dermatologists.…”
Section: Other Dermatological Diseasesmentioning
confidence: 99%
“…All of these works have reported the equivalence between computer and human diagnosis. Besides skin cancer detection, DL is also being successfully applied to other areas of dermatology, such as the monitoring of wound healing (Shenoy et al, 2018), the classification of ulcers (Goyal et al, 2018), and onychomycosis (Han et al, 2018b).…”
Section: Recent Applications To Dermatologymentioning
confidence: 99%
“…9 Since then, numerous authors have studied medical image analysis using CNN with deep learning method. [12][13][14] Most examinations and diagnoses of GI tract diseases are performed using endoscopy. 1,15 Therefore, accurate analysis of endoscopic images is important, and the application of CNN can be considerably useful.…”
Section: Convolutional Neural Network In Endoscopic Imagingmentioning
confidence: 99%